Dynamical systems : Michael Herman memorial volume - Herman, Michael R; Fathi, Albert; Yoccoz, Jean-Christophe (Cambridge : Cambridge University Press, 2006)
'Michael Robert Herman had a profound impact on the theory of dynamical systems over the last 30 years. His seminar at the Ecole Polytechnique had major worldwide influence and was the main vector in the development of the theory of dynamical systems in France. His interests covered most aspects of the subject, though closest to his heart were the so-called small divisors problems, in particular those related to the stability of quasiperiodic motions. This volume aims to reflect the depth and variety of these interests and the frontier of present research; a frontier shaped decisively by Michael Herman's contributions.'--Jacket.
Reprinted from: Ergodic theory and dynamical systems, v. 24, no. 5, 2004.
Includes bibliographical references.
Text in English, some chapters in French.
Keywords: Differentiable dynamical systems; Hamiltonian systems